2012
DOI: 10.7845/kjm.2012.48.1.029
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Fermented Dioscorea batatas Dence by two Stage Fermentation

Abstract: This study was conducted to investigate antioxidative and physiological activities of two stage fermented Chinese Yam (TSFCY) by Monascus sp. MK2 and Lactobacillus brevis HLJ59. The extracts from TSFCY were measured to examine pigments, monacolin K contents, total polyphenol and flavonoid contents, DPPH radical scavenging activity, reducing power, ACE inhibitory activity and GABA contents. In this study, the results show that Monascus sp. MK2 and Lactobacillus brevis HLJ59, with Dioscorea batatas Dence. As the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In this study, Betaphycus gelatinum pretreated with ultrasound-assisted mild acid contained reducing sugars, which were directly used by L. brevis. Meanwhile, L. brevis produced enzymes to degrade macromolecular carbohydrates [ 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Betaphycus gelatinum pretreated with ultrasound-assisted mild acid contained reducing sugars, which were directly used by L. brevis. Meanwhile, L. brevis produced enzymes to degrade macromolecular carbohydrates [ 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fermentation by L. brevis , isolated from maize and sorghum, improved the tannin content and TPC of maize flour with an increasing fermentation period [ 23 ]. L. brevis fermentation increased the TPC, TFC, γ-aminobutyric acid content, antioxidant ability, and angiotensin-converting enzyme inhibitory activity in Chinese yam [ 24 ]. An edible brown seaweed, Saccharina japonica , as the sole carbohydrate source, was fermented by L. brevis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Darwish et al ( 2017 ) and Melani et al ( 2021 ) found that the addition of angkak ( Monascus -fermented rice/red mold rice) did not give a significant effect on the pH value and acidity of yogurt and goat milk kefir respectively. Pyo and Song ( 2009 ) found that the addition of Monascus -fermented soybean decreased the pH and increased the acidity of yogurt, while Jeon et al ( 2011 ) found that the pH of yogurt increased after the addition of Monascus -fermented Chinese yam. Different substrates of Monascus -fermentation will produce different amounts and types of compounds which could affect the characteristics of each Monascus -fermented product.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its functional properties, yogurt has been widely consumed for thousands of years and undergoes constant development to improve its health benefits. One of the most common ways to improve yogurt quality is by adding functional ingredients, such as essential oils (Comunian et al 2017 ), fruits, flowers (Chouchouli et al 2013 ; Marchiani et al 2015 ; Sah et al 2016 ; Liu and Lv 2018 ; Dimitrellou et al 2020 ), green tea and coffee powders (Dönmez et al 2017 ), and Monascus -fermented products (Jeon et al 2011 ; Abdel-Raheam et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation